Implementation of the RAD Method in the Development of a Web-Based Jiwa Baru Village Profile Information System - Firda Fatrika; Fajriyah; Iwan Setiawan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The use of information technology in various aspects of life including government is increasingly important, one of which can feel the positive impact of the application of technology is the village government. In Jiwa Baru Village, the delivery of information is still delivered through speakers or bulletin boards. The limitations in delivering this information often make it difficult for people to get accurate and up-to-date information. The purpose of this study is to design a web-based Jiwa Baru Village Profile Information System which aims to deliver information to the public effectively and efficiently. The method used in this study uses the RAD (Rapid Application Development) method. The results of the evaluation show that all functions of this system run well and in accordance with user needs, with this system it can make it easier for people to find information about the village.